2018
DOI: 10.1002/mp.13281
|View full text |Cite
|
Sign up to set email alerts
|

The influence of nuclear interactions on ionization chamber perturbation factors in proton beams: FLUKA simulations supported by a Fano test

Abstract: Purpose In all recent protocols for the reference dosimetry of clinical proton beams, ionization chamber perturbation factors are assumed to be unity. In this work, such factors were computed using the FLUKA Monte Carlo code for three ionization chamber types, with particular attention to the influence of nuclear interactions. Methods The accuracy of the transport algorithms implemented in FLUKA was first evaluated by performing a Fano cavity test. Ionization chamber perturbation factors were computed for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 28 publications
(57 reference statements)
4
30
0
Order By: Relevance
“…This increase is most pronounced for large cylindrical chambers like the two Farmer chambers NE 2571 and PTW 30013, where the f Ref Figures 6 and 7 show the simulated perturbation correction factors for the investigated cylindrical and plane-parallel ionization chambers, respectively. The perturbation correction factors for the PTW Roos chamber are compared to a study by Lourenço et al 11 Of all the perturbation factors p dis shows the greatest deviation from unity. Figure 6 shows an increase in p dis towards low proton energies for cylindrical ionization chambers.…”
Section: B Monte Carlo Simulated F Qmentioning
confidence: 97%
See 3 more Smart Citations
“…This increase is most pronounced for large cylindrical chambers like the two Farmer chambers NE 2571 and PTW 30013, where the f Ref Figures 6 and 7 show the simulated perturbation correction factors for the investigated cylindrical and plane-parallel ionization chambers, respectively. The perturbation correction factors for the PTW Roos chamber are compared to a study by Lourenço et al 11 Of all the perturbation factors p dis shows the greatest deviation from unity. Figure 6 shows an increase in p dis towards low proton energies for cylindrical ionization chambers.…”
Section: B Monte Carlo Simulated F Qmentioning
confidence: 97%
“…The depth was chosen to slightly differ from the recommendations in the two mentioned codes of practice because this allows a comparison to f Q and k Q determined in the literature. [6][7][8][9]11 Simulations were performed for incident proton energies between 70 MeV (R res = 2.18 cm) and 250 MeV (R res = 36.69 cm). The influence of the positioning method of cylindrical ionization chambers was investigated by simulating the f Q factors under consideration of the EPOM (reference point at depth z Q þ Δz Q ) as well as by placing the chambers with their reference points at the measurement depth z Q .…”
Section: C Monte Carlo Simulations Of P Q and F Qmentioning
confidence: 99%
See 2 more Smart Citations
“…All simulations were performed with full electromagnetic transport (photon and electron transport down to 1 keV) and with the physics models set to the highest precision level (e.g., full Rayleigh and Coulomb scatter corrections, heavy fragment evaporation and coalescence). Recently, a Fano cavity test performed by Lourenco et al [35] showed that the FLUKA code passes the test within 0.15% if the step size in the multiple Coulomb scattering algorithm is set small enough compared to the dimensions of the cavity of interest. Therefore, in order to maximize the transport precision for the simulations FIGURE 2 | FLUKA simulation of the irradiation of a PTW 30013 Farmer ionization chamber in a water phantom with 1 GeV/u 56 Fe ions.…”
Section: Monte Carlo Simulationsmentioning
confidence: 99%